ANALISIS KESULITAN GURU BIOLOGI DALAM IMPLEMENTASI PEMBELAJARAN KURIKULUM 2013 DI SMA KOTA PEKANBARU - Lusiana Meiling; Mariani Natalina; Suwondo ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The aim of this study the analysis of difficulty biology teacher in the learning implementation of curriculum 2013 at senior high school pekanbaru. Collecting data using open questionnaire and interviews. The sample was a biology teacher in class X from 7 high schools (SMA) Public and Private targeted curriculum implementation 2013 school year 2013/2014, amounting to 8 people. The data were analyzed descriptively. The results obtained by the percentage of the difficulties in the implementation of learning a biology teacher at the high school curriculum in 2013 of planning indicators obtained 0.33 (Less experienced difficulty), the implementation of 0,23 (Less experienced difficulty) and assessment 0.48 (Less experienced difficulty). Thus the implementation of the biology of learning that teachers using the curriculum in 2013 less difficult.Keywords: Difficulty, Biology Teacher, Curriculum 2013